MEDIA COVERAGE OF LABOR MIGRATION IN AN ECONOMIC CONTEXT - Norov, Ortiqxo‘ja (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
The article provides a comprehensive analysis of how labor migration is covered in the media within an economic context, as well as its role in shaping public awareness and perceptions of economic processes. The main objective of the study is to identify how the economic significance of labor migration is interpreted in the media space of different countries and to assess the impact of such media coverage on socio-economic perceptions. The article includes a comparative analysis of materials published in the media of Uzbekistan, Russia, and European countries. In particular, it examines the content and analytical depth of information related to the volume of remittances, their impact on currency stability, changes in labor markets, and the investment potential of labor migrants. The research identifies the place these issues occupy in media discourse and highlights differences in approaches across various information environments. Both quantitative and qualitative analysis methods were applied in the study. Specifically, media content was analyzed, and the relationship between media information and actual economic indicators was examined using official statistics and reports from international organizations (World Bank, UN, IOM, IMF). This approach allowed for an assessment of the objectivity of media interpretations and the degree to which the information reflects economic reality. The results indicate that the economic role of labor migrants is interpreted differently in local and foreign media. In some cases, the economic benefits of migration — particularly the macroeconomic significance of remittances and investment opportunities — are insufficiently highlighted, while in other cases the economic impact is presented in a one-sided manner. The article substantiates the need to strengthen the analytical approach in the media, present economic statistics in a clear and comparable format, and develop an information policy that objectively and scientifically reflects the contribution of labor migration to national economic development. The findings of this study have practical relevance for media research, economic journalism, and migration policy.
Keywords: labor migration; migration policy; money transfers; public awareness; currency stability; reintegration; mass media